The integration of sex and gender considerations in health policymaking: a scoping review - Allison Williams; Joonsoo Sean Lyeo; Sophie Geffros; Alexander Mouriopoulos (BMC, 2021)
Abstract While the terms 'sex' and 'gender' represent distinct concepts, their influence may intersect as important determinants of health. Despite their influence in shaping individual health outcomes, there is often inaccuracy and inconsistency in the degree to which sex and gender considerations are integrated in the health policymaking process. This primary aim of this paper is to fill the gap in the current understanding of how sex and gender considerations are integrated in this process. A scoping review methodology was used with the objective of assessing the extent to which sex and gender were considered inclusively and comprehensively in established examples of health policy planning and development. One hundred seventy-five documents from the academic and grey literature were found to meet the inclusion criteria for this scoping review. The authors charted the data from these publications, assessing the ways in which sex and gender were incorporated in their policy development process. Five key findings were ascertained from this review: (1) the terms sex and gender are often used interchangeably; (2) the terms sex and gender are often used with a limited and binary scope; (3) the most inclusive and comprehensive documents included transgender and gender diverse populations; (4) there are significant variations in the degree of inclusivity and comprehensivity of these documents based on geographic distribution; and (5) documents published within the last 5 years were more inclusive than older documents. This paper concludes with an acknowledgment of the limitations of the study design, a summary of the findings, future research directions, and implications for policymakers.